2017
DOI: 10.21315/mjms2017.24.6.14
|View full text |Cite
|
Sign up to set email alerts
|

Embolisation of External Jugular Vein Aneurysm: A Case Report

Abstract: Introduction: Venous aneurysms are not as common as their arterial counterpart. The choice of management is debatable. Case Report: We present the case of a teenage boy with left external jugular vein aneurysm treated by endovascular technique. Embolisation was done using pushable microcoils with access via the femoral vein and direct puncture. Conclusion: This form of treatment provides a less-invasive option with a more concrete evaluation of the venous abnormality and its drainage during venous aneurysm occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Several authors confirmed that anticoagulation alone is insufficient for preventing such complications [ [25] , [26] , [27] , [28] ]. Most patients with external jugular vein aneurysm underwent surgical treatment with local, and general anesthesia [ 16 , [29] , [30] , [31] , [32] , [33] , [34] ].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors confirmed that anticoagulation alone is insufficient for preventing such complications [ [25] , [26] , [27] , [28] ]. Most patients with external jugular vein aneurysm underwent surgical treatment with local, and general anesthesia [ 16 , [29] , [30] , [31] , [32] , [33] , [34] ].…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Noninvasive diagnostic imaging modality like doppler ultrasonography of the neck veins confirms the diagnosis. 12 Further, CT angiography with digital subtraction angiography and MR venography can help to delineate the anatomical extent of the aneurysm, presence of feeder vessels, intraluminal thrombus besides aiding in pre-operative planning, 9,10,13 EJV aneurysms rarely give rise to complications like thrombophlebitis, rupture, thrombus formation secondary to trauma, or pulmonary embolism. 14,15 The indications for treatment are primarily cosmetic and rarely due to complications of the aneurysm per se.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous coil embolization, along with percutaneous injection of sclerosant foam, has recently emerged as a minimally invasive alternative. 9,13 Though there is no evidence, at present, to prove its clinical efficacy compared to standard surgical excision, it offers a superior cosmetic outcome with lesser hospital stay at the expense of incurring higher treatment costs.…”
Section: Discussionmentioning
confidence: 99%
“…Management is commonly indicated for cosmetic reasons or when complications such as thromboembolism, rupture or thrombophlebitis arise 1. While majority of the previously reported cases have been managed with surgical excision, endovascular treatment may be an attractive option as it circumvents the issues and complications of surgery such as need for anaesthesia, potential injury to surrounding structures, wound infection, haemorrhage and scar 2. However, it would be prudent to note that secondary to the scarcity of available literature, no specific guidelines for the treatment of these lesions exist.…”
Section: Descriptionmentioning
confidence: 99%